A new continuum mapping procedure at HartRAO - Büchner, Sarah (Rhodes University, Faculty of Science, Department of Physics)
A basket weaving technique for making radio continuum maps has been developed at the Hartebeesthoek Radio Astronomy Observatory (HartRAO). This data reduction technique significantly reduces scanning effects by using independent maps scanned in orthogonal directions. The observation and data analysis procedures that were developed are presented. The technique was used to map the supernova remnant MSH 15-52 at frequencies of 5000 MHz and 8500 MHz. The flux spectral index for this supernova remnant was found to be 0.83 ± 0.02 in this frequency range. Two regions (A and B) of the Galactic plane were observed at 8500 MHz with a resolution of 6'. Region A covered the 5°x5° area 47.5°< k 52.5°, Ibl < 2.5°, and region B was the 4.2°x3° area 320.4°< I <334.6°, Ibl < 1.5°. Far infrared observations at 60 !lm were used in conjunction with the radio maps to separate the thermal and non-thermal components of the radio emission. The technique can be used to map the Galactic plane at 8500 MHz using dual polarisation once the receiver at HartRAO has been upgraded. This would fulfil a need for a medium resolution, high frequency survey of the southern Galactic plane.,Adobe Acrobat Pro 9.4.6,Adobe Acrobat 9.46 Paper Capture Plug-in
Keywords: Hartebeesthoek Radio Astronomy Observatory; Radio astronomy -- Methodology; Galactic cosmic rays